MATHEMATICAL MODEL OF INPUT DEGRADING FACTORS - Ліпіхін, С. В. (Proceedings of National Aviation University (archive), 2021)
The problem of determining the relations between the outputs of a given linear stationary multidimensional system with a certain set of stationary random input influences is considered. The possibility of replacing random processes at the input of the control system with equivalent deterministic influences in the construction of a mathematical model of input degrading factors is shown.